Desenvolvimento de um sistema embarcado para detecção de nêutrons térmicos e fótons de baixa energia - Geraldo Porto de Araujo (2013)
Europium-activated lithium-6 iodide is a scintillator used for gamma and neutron counting. A portable detection system was built based on this scintillator. This system has three modules: the scintillator, a 10 m liquid light guide, and a Hamamatsu photon counting head H9319 used as a light pulse digitizer. Data transfer, measurement time and other necessary adjustment can be controlled by software from the PC through the RS-232C interface. The scintillator, a crystal of 6LiI(Eu), is a small cylinder with 3 mm diameter and 40 mm length completely sealed in an aluminum tube coupled to the light guide. The small size of the scintillator increases the neutron/gamma count ratio, since 2 to 3 mm of thickness of this crystal absorbs all thermal neutrons. Intensities of X and gamma rays, and thermal neutrons can be recorded for time intervals of 10 ms to 1 s storing up to 10000 countings. The system was calibrated for measuring radiation doses for validating numerical models in dosimetry. Two characteristic reinforce this application, measurements can be done at several meters away from the radiation source and also inside of water. In addition, it was used to build nuclear probes based on Compton scattering or neutron moderation in porous media by attaching an AmBe source to the top of the aluminum tube. Tests were done to determine the reproducibility of counting rates. Background counting was measured at several temperatures to verify the influence of dark current of PMT. Sealed AmBe, low activity Am.